An Integrated and Multibiomarker approach to delineate oxidative stress status of Bellamya bengalensis under the interactions of elevated temperature and chlorpyrifos contamination. (February 2021) - Baag, Sritama; Mahapatra, Sayantan; Mandal, Sumit
Abstract: Synergistic effects of warming on bioconcentration and receptiveness of pollutants are still poorly unravelled in conjunction with cellular and molecular responses. The present study addressed the impact of an environmental relevant dose of chlorpyrifos (organophosphate pesticide), under control (25 °C) and elevated levels of temperature (30 °C, 35 °C) in Bellamya bengalensis, a freshwater gastropod for 60 days across various endpoints. Multiple levels of biomarkers were measured: growth conditions (organ to flesh weight ratio, condition index), oxidative stress status (SOD, CAT, GST, LPO) and DNA damage (Comet assay-3 rd, 30 th and 60 th days only) after acute (24, 48 and 72 h) and long-term exposures (10 th, 20 th, 30 th, 40 th, 50 th and 60 th days). An integrated biomarker response (IBR) strategy was adapted to amalgamate results generated from various biomarkers to assess organism's vulnerability to pesticide pollution and how it may shift with warming climate. Significant changes were observed in growth conditions under longer exposure periods. Acute as well as long-term exposures enhanced the antioxidant and detoxification enzyme activity. DNA damage was extensive under longer exposure to stress howbeit was also significantly escalated under acute severe warming. Antioxidant and detoxification mechanisms fell short in counteracting cellular level damage. The IBR results indicated long-term acclimation of B. bengalensis to elevated temperatures and pesticide contamination lead to an improved tolerance level howbeit, acute stress was more detrimental. This study provided evidence for the efficiency of employing an integrated biomarker approach for B. bengalensis in future bio-monitoring studies. Highlights: Results deciphered a significant effect of warming than pesticide contamination. Acute warming reflected vulnerability towards extreme climatic events. Long term studies reveal a scope for resilience against applied stressors.